2021
DOI: 10.1159/000518050
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Cysts after Endoscopic Ultrasonography-Guided Ethanol and/or Paclitaxel Ablation Therapy: Another Mimic of Pancreatic Pseudocysts

Abstract: <b><i>Background:</i></b> Endoscopic ultrasound-guided ablation (EUS-A) therapy is a minimally invasive procedure for pancreatic-cystic tumors in patients with preoperative comorbidities or in patients who are not indicated for surgical resection. However, histopathologic characteristics of pancreatic cysts after ablation have not been well-elucidated. <b><i>Methods:</i></b> Here, we analyzed pathological findings of 12 surgically resected pancreatic cysts after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Moreover, from the 36 recorded severe adverse events, 31 (86.1%) occurred after ethanol or ethanol/paclitaxel ablation. In addition to the reported complications, chemoablation was reported as associated with the development of new cysts, similar to pseudocysts, with specific radiological and histological characteristics [43]. Choi et al [42] in their patient cohort treated with ethanol, indicated that SB-IPMNs, multilocular cysts, suspected ethanol leakage during the procedure, and increased cystic fluid viscosity were independently associated with pancreatitis, however their conclusions were not confirmed by other reports.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, from the 36 recorded severe adverse events, 31 (86.1%) occurred after ethanol or ethanol/paclitaxel ablation. In addition to the reported complications, chemoablation was reported as associated with the development of new cysts, similar to pseudocysts, with specific radiological and histological characteristics [43]. Choi et al [42] in their patient cohort treated with ethanol, indicated that SB-IPMNs, multilocular cysts, suspected ethanol leakage during the procedure, and increased cystic fluid viscosity were independently associated with pancreatitis, however their conclusions were not confirmed by other reports.…”
Section: Discussionmentioning
confidence: 93%
“…In recent years, the "ethanol-free" ablation technique has been proven to be safer and more effective in certain hepatic and pancreatic cystic lesions. It has also demonstrated the ability to reduce the incidence of adverse reactions [20][21][22][23] . Building upon previous studies, our hypothesis was that "alcohol-free" ablation could be equally applicable to solid tumors of the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…While these prior studies sought to measure the efficacy and durability of EUSguided intratumoral drug delivery based on post-procedural radiographic cyst resolution, An et al [65] recently reported the histopathologic characteristics of 12 surgically resected PCNs following EUS-guided local ablation with ethanol and/or paclitaxel. Based on pretreatment imaging, a majority (84%) of these lesions were believed to be MCNs, with a mean cyst size that was similar pre-and post-procedure.…”
Section: Eus-guided Intratumoral Drug Delivery For the Treatment Of Pcnsmentioning
confidence: 99%